A Founder on Founding: Jefferson’s Advice to Koraes - Evrigenis, Ioannis D. (The Historical Review/La Revue Historique, 2005)
In 1823, shortly after the outbreak of the Greek Revolution, and in the context of a general attempt to gather support for the Greek cause, Adamantios Koraes wrote to Thomas Jefferson, whom he had met once in Paris, to request his advice on the founding of a Greek state. Although brief, the exchange between the two men provides a rare, if not unique, record of a founder’s advice to an aspiring emulator. Koraes’ role in Greek political and intellectual life, coupled with Jefferson’s fame, have made the correspondence between the two men a source of some interest among Greek scholars, but Jefferson’s advice has never been studied in the context of his broader political theory. This paper traces the history of the acquaintance of the two men and of their subsequent correspondence, and places Jefferson’s recommendations in the context of his political thought. Written as it was with the benefit of a long life in politics and more than forty-five years of experience from the American founding, Jefferson’s advice to Koraes provides a singular opportunity to assess his political ideas over time.